Campur Kode pada Konten Selebgram Bali - Manik Warmadewi Anak Agung Istri; Anak Agung Gede Suarjaya; I Gusti Ayu Agung Dian Susanthi; I Wayan Pranata Putra (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
The code-mixing discussed in this research is focused on the use of two or more languages in code-mixing in the speech of Balinese celebrities/influencers. The purpose of this research is to find out what forms of code mixing occur in the speech of Balinese celebrities and what elements are mixed in code mixing by Balinese celebrities. This research is based on the theory of code-mixing by Muysken (2000). Qualitative method is applied in this research. The data collection techniques used in this research are listening, note-taking, and documentation methods. Qualitative method is used to analyze the data in this study. The results of the analysis are presented using informal method where each data will be presented with explanatory sentences below it regarding the results of data analysis in a detailed and structured manner. The results show that all types of code-mixing (insertion, alternation, and congruent lexicalization) are found in Balinese Selebgram utterances; The elements mixed in Balinese Selebgram utterances are words, phrases, and clauses in all types of code-mixing.